Technostress in a multiorganizational work environment - Brandt, Emma (2022)
Technostress has been widely studied and with even more focus on the employee’s personal life during the past decade. According to current research technostress can cause both psychological and physiological symptoms and experiences with technostress at work can easily reflect on an individual’s personal life. The negative consequences of technostress can lead to lack of motivation, impaired well-being at work and in worst case scenarios even to burnout. Even though there has already been various research covering technostress and mitigating methods, that is yet to be studied is organizations that use ICT and IS systems from different organizations in their everyday work. This Master’s thesis focused on studying technostress in a multiorganizational work environment in an organization that employs over a hundred employees in Finland. The employees of the case organization used two different sets of laptops provided by different companies that had to be used by the employees at all times. The goal of this research was to understand how the employees experienced that the use of two laptops at work contributed to their experience of technostress and how the employees were able to cope with the pressure of using two laptops. Teleworking and its impact on the use of two laptops was also studied in the thesis. In addition, the research focused on three different leveled roles in the case organization as previous research literature has shown that employees in higher roles experience more technostress than others. The main findings of this thesis showed that using two laptops at work had a significant impact on the creation of technostress at work and the workload and interruptions at work. The findings showed that the challenge in using two laptops caused both software related and hardware related stressors for the employees, that depending on the role experienced different types of stress symptoms and consequences. As this type of work environment had not been researched before, this thesis contributed to current research with a new type of context of studying technostress.